Two new isoquinoline alkaloids from the seeds of Nandina domestica. Issue 19 (2nd October 2021) - Qin, Juan; Zhang, Sheng-Yuan; Zhang, Yu-Bo; Chen, Li-Feng; Chen, Neng-Hua; Wu, Zhong-Nan; Luo, Ding; Wang, Guo-Cai; Li, Yao-Lan
Abstract: Two new isoquinoline alkaloids, 6  R, 6a S - N -nantenine Nβ -oxide (1 ), 6 S, 6a S - N -nantenine Nα -oxide (2 ), along with nine known alkaloids, nantenine (3 ), oxonantenine (4 ), protopine (5 ), nornantenine (6 ), N -methyl-laurotetanine (7 ), isocorydine (8 ), O -methyflavinantine (9 ), N -methyl-2, 3, 6-trimethoxymorphinan-dien-7-one Nβ -oxide (10 ) and (+)-10- O -methylhernovine Nβ -oxide (11 ) were isolated from the seeds of Nandina domestica. Their structures were elucidated by extensive analyses of spectroscopic data (IR, UV, HRESIMS, 1 D and 2 D NMR), ECD calculation and comparison with the related literatures. In addition, the cytotoxicity against A549 cells of these alkaloids was determined by the MTT assay. Graphical Abstract: UF0001